A multidisciplinary approach to optimising the virtual management of haemophilia: a roundtable meeting of UK experts - Benson Gary; Bhandari Trupti; Gomez Keith; Holder Kerry-Ann; Stephensen David; Wilkinson Alice; Mangles Sarah (The Journal of Haemophilia Practice, 2023)
The necessity of a multidisciplinary team (MDT) approach in haemophilia care is well recognised globally, with international guidelines advocating this. Prior to the coronavirus disease 2019 pandemic, virtual MDT haemophilia care was gaining support worldwide. However, the pandemic necessitated the rapid implementation of innovative virtual solutions to ensure continued access to multidisciplinary care. A multidisciplinary panel of healthcare professionals who specialise in haemophilia care in the United Kingdom gathered to discuss the following: the current landscape of haemophilia MDT care and best practices, the benefits, challenges, and opportunities for virtual MDT care, managing bleeds remotely, virtual paediatric care, and the future of virtual MDT care. The consensus was that virtual MDT care is widely used, however formats vary depending on the healthcare setting, available resources, MDT preferences, and local policy. Advisors agreed that virtual MDT care has several benefits, such as improved convenience/choice for their patients and wider patient reach. However, many patient-specific and logistical challenges exist. Hybrid care models may provide an opportunity to overcome these challenges. The decision on how bleeds are managed (virtually versus face-to-face) depends on provider preference, the patient-provider relationship, and the patient’s disease severity, history, and ability to self-manage. As such, this should be assessed on a case-by-case basis. Virtual tracking tools cannot be solely relied upon for MDT decisionmaking as patient accuracy cannot be ascertained. The MDT composition for paediatric care should be tailored to the patients’ and their parents’/caregivers’ needs. Lastly, hybridised care will likely be adopted for future haemophilia management and will facilitate the advancement of MDT care.